Stepwise reduction of a base-stabilised ferrocenyl aluminium(iii) dihalide for the synthesis of structurally-diverse dialane species. Issue 33 (9th August 2022) - Dhara, Debabrata; Fantuzzi, Felipe; Härterich, Marcel; Dewhurst, Rian D.; Krummenacher, Ivo; Arrowsmith, Merle; Pranckevicius, Conor; Braunschweig, Holger
Abstract : A bulky ferrocenyl-based NHC-stabilised aluminium(iii ) dihalide was reduced in different solvents, leading to vastly different outcomes, including formation of a rare example of a dialane and a novel dialuminyl analogue of the Birch reduction. Abstract : We report the reduction of bulky ferrocenyl-based NHC-stabilised aluminium(iii ) diiodide [Fc*(NHC)AlI2 ] (Fc* = 2, 5-bis(3, 5-di- tert -butylphenyl)-1-ferrocenyl) in different hydrocarbon solvents (hexane, benzene, toluene, and p -xylene), which results in different outcomes. Reduction in hexane with an equivalent amount of KC8 generates the diiododialane [(Fc*(NHC)AlI)2 ], whereas complete reduction in hexane leads to an unusual C–H activation at an N–Me group of one NHC unit. In contrast, reaction in aromatic solvents result in hitherto unknown Birch-type reductions of the corresponding solvent molecules by transient aluminium radicals of the type [LAlR2 ]˙, which is ultimately bound to two aluminium centers.